Worker's health from the perspective of managers of a Federal Public University (Research, Society and Development, 2019)
The lack of knowledge in the health of the worker allied to the exercise of ineffective managerial practices can hinder the delimitation of the epidemiological profile of the workers, making prevention and care actions necessary. This article identified the main reasons for the removal of servers from the academic units / agencies of a Federal Public University in the year 2017 and the knowledge of the managers of these units on workers' health and their management practices. In order to obtain the data on departures, we searched for records of medical records and the medical expertise module of the server's health. To identify knowledge and management practices a semi-structured questionnaire composed of 34 questions was used. Descriptive analysis of the data was carried out in the form of absolute and relative frequency. A total of 37 managers of academic units / agencies participated in the study, where it was identified that 89.2% of the participants did not present any training courses in management and 91.9% in management of workers' health, which may negatively impact practice management practices. Most of the server departures were related to musculoskeletal diseases (15.4%) and mental disorders (12.6%). The training of workers' health managers can improve knowledge and favor the implementation of preventive actions by the institution